Team Re-CIP: a learning model to overcome academic plagiarism among university students / Bayu Kurniawan ... [et al.] - Kurniawan, Bayu; Mat Lazim, Mohamed Jefferi; Wahyuningtyas, Neni; Purnomo, Agus; -, Idris (Universiti Teknologi MARA, 2023)
Academic plagiarism is still prevalent and should be kept away from students' mindsets. This paper aims to develop a learning model for the Team Re-CIP that seeks to overcome academic plagiarism in universities. This study employed the research and development (R&D) techniques in conjunction with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The development stage of the learning model is based on the findings of a needs assessment conducted with 208 students. Two learning experts validated the initial design of the learning model. The findings indicated that practically every student had engaged in academic plagiarism. There is even a strong likelihood that they will always commit plagiarism. However, they have a solid desire to shun plagiarism. Therefore, building a learning model for Team Re-CIP is very important. The primary syntax of this learning approach is reviewing, checking, investigating, presenting, and paraphrasing. Students are divided into numerous groups according to the subject of the content for which they are responsible for writing a paper. This strategy is distinctive because it includes a group called the Re-CIP Team that acts as a peer assessment.